Analysis of Earthquake Information in Palu from Social Media X (Twitter) in the Perspective of Geography Learning - Maulana, Akbar; Arif, Nursida; Putra, Exsa (JPG (Jurnal Pendidikan Geografi), 2026)
The earthquake that struck Palu and surrounding areas on September 28, 2018 triggered extensive information dissemination on social media, particularly on platform X (formerly Twitter). However, the characteristics of disaster related information shared by users and its potential use in geography learning have received limited attention. This study aims to analyze the distribution and characteristics of information related to the Palu earthquake on Twitter and examine its potential as contextual material for geography education. This research employed qualitative content analysis supported by descriptive quantitative data. Tweets containing the keywords “Gempa Palu”, “#GempaPalu”, and “#PrayForPalu” posted between September 28 and October 31, 2018 were collected using the Twitter API and processed with Google Colab. After the data cleaning process, 117 relevant tweets were analyzed based on information type, temporal patterns, spatial references, and sentiment tendencies. The results show that reports on damage and victims were the most dominant content 41,03%, followed by official information and aid related activities. Temporal analysis indicates that tweet activity peaked on the first day after the disaster, while spatial references were mainly associated with Talise, Petobo, and Donggala. Sentiment analysis reveals that neutral posts accounted for 82,4% of the data, indicating that Twitter was primarily used to disseminate factual information during the disaster. These findings highlight the potential of social media data as contextual learning resources to support spatial analysis and disaster literacy in geography education.